MINI REVIEW: PEMANFAATAN ADSORBEN ARANG AKTIF CANGKANG TELUR TERHADAP LOGAM BERAT - Sarah Nur Aulia Azzahra; Soerja Koesnapardi; Ika Yekti Liana Sari (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
A mini review on the utilization of activated carbon adsorbent from eggshells for heavy metal removal has been conducted. From the study results, it is known that activated carbon made from eggshells contains chemical compounds such as calcium carbonate (CaCO₃) at 94%, magnesium carbonate (MgCO₃) at 1%, and calcium phosphate (Ca₃(PO₄)₂) at 4%. The process of making activated carbon from eggshells involves first physically activating the eggshell powder through heating, followed by chemical activation using various strong acids such as HCl. The material is then neutralized and dried at 100°C for 30 minutes. The resulting activated carbon is then brought into contact with heavy metals such as Lead (Pb), Cadmium (Cd), Copper (Cu), Zinc (Zn), and Iron (Fe). The results show that the adsorption percentage and adsorption capacity of the eggshell activated carbon range from 32.09% to 99.81% and 67.745%, respectively. These values are influenced by factors such as surface area, concentration, stirring speed, and the activation conditions of the adsorbent. Keywords: Activated Carbon, Adsorption, Heavy Metals